Treatment of Coronary Artery Disease: Randomized Trials on Myocardial Revascularization and Complete Arterial Bypass Grafting - Rastan, Ardawan J. (The Thoracic and Cardiovascular Surgeon, 2017)
Friedrich Wilhelm Mohr from the very beginning of his career as a cardiac surgeon was involved in the refinements of coronary artery bypass grafting (CABG). At the Leipzig Heart Center, his spirit of early adapting to new technologies inspired the entire team and led to a matchless scientific atmosphere to find solutions to improve almost all fields of cardiac surgery, including CABG. In combination with a tremendous number of patients with indications for isolated coronary artery bypass Prof. Mohr as the surgical principle investigator and the Leipzig Heart Center were able to include patients in the Synergy between PCI [percutaneous coronary intervention] with Taxus and Cardiac Surgery (SYNTAX) trial, the first randomized trials comparing CABG and PCIs using the drug-eluting stents. Final SYNTAX results after 5 years gave direction and scientific evidence for contemporary European revascularization guidelines. These guidelines recommend PCI as an alternative first-line treatment option in patients with coronary three-vessel disease and left main stenosis having low coronary complexity based on the angiographic SYNTAX score. However, the study demonstrated the significant superiority of CABG over PCI in all other patients, especially in these with complex three-vessel disease. The specific characteristic of the SYNTAX study is that the distinguished results were confirmed by several post-SYNTAX comparative randomized trials on coronary revascularization including left main disease and clinical registries even when contemporary drug-eluting stent designs were used. When performing CABG the question of the best second graft remains unclear. While several mono-institutional reports and large meta-analyses demonstrated clear superiority in terms of long-term survival when using bilateral mammary versus single mammary revascularization, this benefit could not be confirmed in randomized trials after 5 years.
Keywords: coronary artery bypass surgery; review; syntax trial; PCI vs CABG